BAKHTIN E PÊCHEUX: LEITURA DIALOGADA (Polifonia, 2013)
Este artigo faz uma leitura dialogada entre Bakhtin e Pêcheux, a partir de dois textos fundadores de suas obras: Análise Automática do Discurso, de Pêcheux, publicado em 1969, e Marxismo e Filosofia da Linguagem, de Bakhtin/Voloshinov, publicado em 1929, com o objetivo de aproximar o pensamento dos dois autores em relação ao seu entendimento do lugar ocupado pelos sujeitos na interação verbal e à ideologia de base marxista.PALAVRAS-CHAVE: Bakhtin, Pêcheux, análise do discursoABSTRACT: This paper aims to establish a dialogical reading between Bakhtin and Pêcheux, especially through two important texts which constitute the basis of their works: Pêcheux’s Automatic Discourse Analisys, published in 1969, and Bakhtin/Voloshinov’s Marxism and the Philosophy of Language, written in 1929, in order to put their ideas together, concerning the way they comprehend the place occupied by the subject in verbal interaction as well as the manner marxist ideology influenced their thoughts.Keywords: Bakhtin, Pêcheux, discourse analysis